Implementasi Metode Regresi Linier dalam Mengukur Kompensasi terhadap Kinerja Karyawan - Mendoza, Muhammad Dominique (LPPM UNIKA Santo Thomas Medan, 2020)
The performance of harvester employees is one of the reasons for the non-achievement of the production target of PT Perkebunan Nusantara IV's North Region of Adolina Unit, where the harvest capacity of harvester employees is still below the stipulated level. Some things that really need to be considered in looking for problems that occur in connection with this decline in performance are the Human Resources issues. the reason for the focus of discussion on Human Resources (HR) because HR is the greatest resource for a company that is very difficult to control compared to other resources. Because HR is not good will result in performance that is not optimal for the company. So it can be suspected that the decline in company performance is caused by the HR factor owned by the company which is not maximally empowered. The value of compensation in this study was calculated using linear regression to performance and it can be concluded that there is an effect of compensation on performance. The value of the compensation coefficient on performance is significant.